2013
DOI: 10.1136/bjsports-2013-092764
|View full text |Cite
|
Sign up to set email alerts
|

Yin and yang, or peas in a pod? Individual-sport versus team-sport athletes and altitude training

Abstract: The question of whether altitude training can enhance subsequent sea-level performance has been well investigated over many decades. However, research on this topic has focused on athletes from individual or endurance sports, with scant number of studies on team-sport athletes. Questions that need to be answered include whether this type of training may enhance team-sport athlete performance, when success in team-sport is often more based on technical and tactical ability rather than physical capacity per se.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 88 publications
(112 reference statements)
0
8
0
Order By: Relevance
“…Physical fitness is of critical importance to several sports, particularly in individual sports. For individual sport athletes (ISA), adequate levels of explosive strength, maximal strength, sprinting, acceleration, deceleration, change of direction, and endurance, are key factors potentially affecting athlete’s performance ( Aughey et al, 2013 ; Coyle, 1995 ; Kovacs, 2006 ). Several training methods are routinely used by ISA in order to boost physical fitness, such as plyometric jump training (PJT) ( Bazyler et al, 2015 ; Ebben, Hintz & Simenz, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Physical fitness is of critical importance to several sports, particularly in individual sports. For individual sport athletes (ISA), adequate levels of explosive strength, maximal strength, sprinting, acceleration, deceleration, change of direction, and endurance, are key factors potentially affecting athlete’s performance ( Aughey et al, 2013 ; Coyle, 1995 ; Kovacs, 2006 ). Several training methods are routinely used by ISA in order to boost physical fitness, such as plyometric jump training (PJT) ( Bazyler et al, 2015 ; Ebben, Hintz & Simenz, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sprinting over a short distance is a common and important event in youth sport [57] and Mendez-Villanueva et al [43] observed youth soccer players to reach speeds of up to 29.5 ± 1.4 (km • h − 1 ) in matches. Additionally, straight sprints have been shown to be the most common type of movement prior to goal-scoring [3,16].…”
Section: Introductionmentioning
confidence: 99%
“…The athletic aerobics athletes must meet the technical requirements of the rules specified in the rules when completing the set of movements. The difficulty of the action is not well controlled, etc [7][8][9][10] . The knee joint is damaged.…”
Section: Introductionmentioning
confidence: 99%